Earth quake disaster mitigation (EQDM) through engineering design. (2020) - Srividhya, K.; Mohan, A.; Tholkapiyan, M.; Arunraj, A.
Abstract: Frequent earthquake disasters in our country have clearly illustrated the need for immediate action in all aspects. Natural disasters are certain to happen, but it is certainly possible to mitigate the effects of disasters. Here we attempt to obtain best possible methods and measures for earth quake disaster mitigation through engineering approach at a micro level. Earthquake disaster mitigation and management are two different aspects when dealing with disaster preparedness. While mitigation efforts precede the disaster event, the management (post disaster event) can be done only by authorities with resources and control over various departments. Rather than spending money on relief after disaster, investments in pre-preparedness will always lead to reduced effects and yield sustainable development generating awareness and confidence among the people. In our present study,  Chennai is considered from among the likely disaster zones in India. Possible mitigation measures are highlighted with particular reference to earthquake resistant foundation design for buildings and structures. Apart from the dedicated design and implementation, public cooperation and discipline are more important for reaping the full benefits during the times of crisis. The ideas developed in this paper will certainly go a long way to enhance capabilities of students of Engineering and Architecture to create awareness and help them consider mitigation measures at a micro level while planning and implementing any new project.